THE IMPORTANCE OF ICT ON KNOWLEDGE MANAGEMENT IN ORGANIZATIONS - N., . Seifollahi (university of eloued جامعة الوادي, 2018)
knowledge management (KM) is a process that transforms individual knowledgeinto organizational knowledge.Knowledgeis information that is meaningful in cognitive forms such as understanding, awareness and ability .It is typically acquired by experience, information consumption, experimentation and thought processes such as imagination and critical thinking. communication and information technology(ICT) are technologies which facilitate the management to share knowledge and information .thus ,ICT have a prominent role on knowledge management initiatives. One of the key issues in KM is the role of communication and information technology. this is important from two points. the first is that ICT has played a central role in the primary literature of knowledge management. Second, ICT plays a prominent role in many early knowledge management initiatives. In thisarticle,the importance and role of information technology in knowledge management in organizations has been investigated and analyzed.
artical
Keywords: Information and Communication, Knowledge Management Processes Organizational The objectivist and practice-based perspective